Genetic dissection of flowering time in Brassica rapa responses to temperature and photoperiod. (March 2019) - Xiao, Dong; Shen, Hao-Ran; Zhao, Jian-Jun; Wei, Yan-Ping; Liu, Dong-Rang; Hou, Xi-Lin; Bonnema, Guusje
Highlights: We identified flowering-time QTL (fQTL) in different photoperiod and temperature regimes in the greenhouse, and studied their colocation with known flowering time genes. Under all environmental conditions tested the major fQTL that mapped to the BrFLC2 _A02 locus was detected, however its effect decreased when plants were grown at low temperatures. The vernalization treatment decreased expression of all BrFLC paralogues in the parental lines, and showed the lowest transcript level after 28 days of vernalization. Transcript abundance of BrFLC3 _A03 and BrFLC5 _A03 was repressed much stronger and already reached lowest levels after 14d in the early-flowering type YS-143. Abstract: The Brassica rapa ( B. rapa ) species displays enormous phenotypic diversity, with leafy vegetables, storage root vegetables and oil crops. These different crops all have different flowering time, which determine their growing season and cultivation area. Little is known about the effects of diverse temperature and day-lengths on flowering time QTL associated with FLC paralogues. We phenotyped the flowering time of a doubled haploid population, established from a cross between Yellow sarson and Pak choi under diverse environmental conditions. We identified flowering-time QTL (fQTL) in different photoperiod and temperature regimes in the greenhouse, and studied their colocation with known flowering time genes. As several fQTL colocalized with FLC paralogues, we studied the expression patterns of four FLC paralogues during the course of vernalization in parental lines. Under all environmental conditions tested the major fQTL that mapped to the BrFLC2 _A02 locus was detected, however its effect decreased when plants were grown at low temperatures. Another fQTL that mapped to the FLC paralogue, BrFLC5 _A03 was also identified under all tested environments, while no fQTL colocated with BrFLC1 _A10 or BrFLC3 _A03. Furthermore, the vernalization treatment decreased expression of all BrFLC paralogues in the parental lines, and showed the lowest transcript level after 28 days of vernalization. Transcript abundance stayed low after returning the plants for seven days to normal growth temperature. Interestingly, transcript abundance of BrFLC3 _A03 and BrFLC5 _A03 was repressed much stronger and already reached lowest levels after 14d in the early-flowering type YS-143. This study improves understanding of the effects of daylength and vernalization on flowering time in B. rapa and the role of the different BrFLC paralogues therein.